Problems of remote detection of chemical explosives and fissile materials using neutron-activation diagnostics method - Dubina, V.N.; Chornyj, A.V.; Chornyj, V.V. (Вопросы атомной науки и техники, 2014)
This paper presents results of computer simulation of nuclear processes (using Geant4 9.0 package) for neutrons passing through a shell-free explosive model and through a model of military load containing some fissile material. Spectral distributions of γ-quanta were calculated for the neutron with fixed energy at different points of time after irradiation. The programs were designed using C++ and function under execution control of OS Red Hat LINUX 6.2 FEDORA. Представлены результаты компьютерного моделирования с использованием пакета Geant4-09 ядерно-физических процессов прохождения нейтронов через безоболочечную модель взрывчатого вещества, а также через модель боезаряда с делящимся веществом. Рассчитаны спектральные распределения γ-квантов для фиксированной энергии нейтронов в различные моменты времени после облучения.. Программы разработаны на языке C++ и работают под управлением OS Red Hat LINUX 6.2 FEDORA Представлено результати комп'ютерного моделювання з використанням пакету Geant4-09 ядерно-фiзичних процесiв проходження нейтронiв через модель вибухової речовини без оболонки, а також через модель боєзаряду з подiльчим матерiалом. Розрахованi спектральнi розподiли γ-квантiв для фiксованої енергiї нейтронiв у рiзнi моменти часу пiсля опромiнення. Програми розробленi на мовi C + + i працюють пiд управлiнням OS Red Hat LINUX 6.2 FEDORA.